2003
DOI: 10.1038/nn1045
|View full text |Cite
|
Sign up to set email alerts
|

The p75 receptor acts as a displacement factor that releases Rho from Rho-GDI

Abstract: The neurotrophin receptor p75(NTR) is involved in the regulation of axonal elongation by neurotrophins as well as several myelin components, including Nogo, myelin-associated glycoprotein (MAG) and myelin oligodendrocyte glycoprotein (OMgp). Neurotrophins stimulate neurite outgrowth by inhibiting Rho activity, whereas myelin-derived proteins activate RhoA and thereby inhibit growth. Here we show that direct interaction of the Rho GDP dissociation inhibitor (Rho-GDI) with p75(NTR) initiates the activation of Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
371
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(382 citation statements)
references
References 28 publications
6
371
1
3
Order By: Relevance
“…Recently, several proteins were reported to interact with either RhoA protein or its regulators indicating a similar sequestration mode of action. For example, p75 neurotrophin receptor could facilitate the release of prenylated RhoA from Rho-GDI by targeting Rho-GDI (Yamashita and Tohyama, 2003). A similar observation was reported with the ERM (ezrin/radixin/moesin) protein, which could also function as a Rho-GDI displacement factor to induce activation of RhoA in Swiss 3T3 cells (Takahashi et al, 1997).…”
Section: Discussionsupporting
confidence: 64%
“…Recently, several proteins were reported to interact with either RhoA protein or its regulators indicating a similar sequestration mode of action. For example, p75 neurotrophin receptor could facilitate the release of prenylated RhoA from Rho-GDI by targeting Rho-GDI (Yamashita and Tohyama, 2003). A similar observation was reported with the ERM (ezrin/radixin/moesin) protein, which could also function as a Rho-GDI displacement factor to induce activation of RhoA in Swiss 3T3 cells (Takahashi et al, 1997).…”
Section: Discussionsupporting
confidence: 64%
“…By contrast, it has also been reported that Rho only associates with p75 NTR and becomes active on binding of Mag to the receptor complex 37 . More recently, it was reported that p75 NTR interacts only indirectly with Rho by binding to and displacing Rho-GDP dissociation inhibitor (Rho-GDI), thereby activating Rho 65 .…”
Section: R E V I E W Smentioning
confidence: 99%
“…These studies further validate Rho signaling as an important element in the attenuation of anti-cancer drug induced neurotoxicity. Since Rho GTPases are now well established as a convergence point downstream of p75 NTR in the regulation of neurite outgrowth (Domeniconi et al, 2005;Yamashita and Tohyama, 2003;Yamashita et al, 1999;Yamauchi et al, 2004), we propose that the inhibition of p75 NTR activation of Rho GTPases is important to maintain normal neuronal morphology during anti-cancer drug exposure.…”
Section: Discussionmentioning
confidence: 96%